Diseño y elaboración de un sistema de gestión ambiental basado en la norma ISO 14001:2015 para florícolas. - Zapata Tello, María José (2023)
This thesis refers to the proposal made for the design and development of an environmental management system (SGA) based on the ISO 14001:2015 standard for flower growers, the environmental management points managed by the company, the Conflicts regarding environmental standards, their regulations regarding resources such as water, land and air quality, as well as the material and human resources that are part of the company. The information that has been collected in a methodological and organized way has allowed the study to have the necessary tools to design a system that has an adequate environmental policy, procedures according to the activities that the company develops, efficient instructions, lists and records that will provide the company a referenced framework to protect and care for the environment in a responsible and friendly way. Therefore, with the application of the ISO 14001:2015 standard, it will allow us to have a standard in terms of proper environmental management, thus ensuring that the organization implements and maintains an EMS. Guaranteeing, autonomously, its compliance due to the established environmental policy. All the steps taken have made it possible to efficiently and effectively meet the stated goal of designing an EMS that is based on the different requirements of the ISO 14001:2015 Standard for floriculture, thus consolidating the basis of the EMS implementation process in the short term. , reducing the impacts and supporting environmental protection.